Association of Patterns of Otoferlin variant A1090E with Ethnicity, Developmental Milestones and Onset of Disease Course in Children with Non-Syndromic Hearing Loss - Riaz, Isma; Rashid, Amir; Arif, Amena; Mushtaq, Iffat; Baig, Zunaira Ali; Ahmed, Naeema (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the association of variant genotypes with ethnicity, developmental milestones and onset of disease course in children with non-syndromic hereditary hearing loss. Study Design: Case-control study. Place and Duration of Study: ENT Department, Combined Military Hospital, Rawalpindi and CREAM Lab-I, Army Medical College, Rawalpindi, Pakistan from Jan to Dec 2022. Methodology: The study enrolled 200 subjects, aged 06 months to 10 years: 100 subjects with non-syndromic hearing loss (NSHL) were placed in Group-A, and 100 healthy individuals in Group-B. Blood samples were collected from each enrolled subject. DNA was extracted followed by polymerase chain reaction, and restriction fragment length polymorphism. Chi-square test was applied to check for association. Results: Analysis of the results indicated ethnicity regions as follows: Punjab 71% (NSHL) and 72% (controls); Khyber Pakhtunkhwa (KP) 19% (NSHL) and 15% (controls); Islamabad (Capital region) 06% (NSHL) and 05% (controls); Sindh 03% each (NSHL & controls) and Baluchistan 01% (NSHL) and 05% (controls). The wild genotype GG was the most common amongst subjects of all regions with highest frequency in Awan caste, both in case and control subjects. Statistically significant (p-value<0.005) difference was observed in NSHL subjects as compared to controls. There was no statistical significance observed between ethnicity and the wild genotype GG, heterozygous genotype GA and mutant genotype AA. Conclusion: In non-syndromic hearing loss (NSHL), the Otoferlin variant A1090E was found to be significantly associated with regional backgrounds among cases. The variant may play a protective role in subjects against NSHL.